ত্রয়ী মনীষীর সমবায় ভাবনা ও তার বিশ্লেষণ - বিশ্বাস, সমীর কুমার
On cooperative movement in Indian subcontinent with reference to the views of Rabindranath Tagore, 1861-1941, Bengali author, Prafulla Chandra Ray, 1861-1941, Bengali chemist and Akhter Hameed Khan, social scientist, on cooperation.